The entrepreneur's mode of entry: Business takeover or new venture start? - Simon C. Parker; C. Mirjam van Praag (Max Planck Institute of Economics, 2006)
We analyse the decision to become an entrepreneur by either taking over an established business or starting a new venture from scratch. A model is developed which predicts how several individual- and firm-specific characteristics influence entrepreneurs'entry mode. The new venture creation mode is associated with higher levels of schooling and wealth, whereas managerial experience, new venture start-up capital requirements and risk promote the takeover mode. Entrepreneurs whose parents run a family firm are predicted to invest the least in schooling, since schooling reduces search costs and these individuals have the lowest probability of needing to search for a business opportunity outside their family. A sample of data on entrepreneurs from the Netherlands provides broad support for the theory; implications for policy-makers concerned about the survival of family firms lacking within-family successors are discussed.
Keywords: 330